UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEAKTIFAN SISWA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) KELAS III SD NEGERI KINTELAN 1 YOGYAKARTA - Rizky Anggalia Kusuma; Danuri (STKIP Subang, 2024)
This study aims to determine (1) the implementation of learning, (2) critical thinking skills, and (3) student activity with the Realistic Mathematics Education (RME) approach in mathematics learning at Kintelan 1 Elementary School. This type of research is Classroom Action Research (CAR) which is carried out in two cycles consisting of four stages in each cycle, namely planning, implementation, observation, and reflection. The subjects of this study were grade III students of Kintelan 1 Elementary School Yogyakarta in the 2024/2025 academic year, totaling 16 students consisting of 10 females and 6 males. The research instruments include observation, tests, and questionnaires. The analysis used in this study is descriptive analysis both qualitatively and quantitatively. The results of the study showed (1) there was an increase in the implementation of learning with the Realistic Mathematics Education (RME) approach in mathematics learning, the average precycle meeting was still low at 53%, the average meeting I cycle I was 78%, continued with the second meeting of cycle I to 89%, then continued with the first meeting of cycle II, the increase was again with an average of 86%, and finally the second meeting of cycle II was 95%, (2) critical thinking skills through the Realistic Mathematics Education (RME) approach in the pre-cycle obtained a test completion percentage of 32% (low), in cycle 1 it increased with a test completion percentage of 62% (high), continued with cycle II there was an increase in completion of 94% (very high), (3) student activity with the Realistic Mathematics Education (RME) approach in the pre-cycle, the percentage of activity was 50% (less category) then cycle I experienced an increase with a percentage of 72% (good category), continued with cycle II there was another increase with a percentage of 81% (very good category). Keywords: Critical Thinking, Student Activeness, Realistic Mathematics Education (RME) Approach.